EFEKTIFITAS BANTUAN LANGSUNG TUNAI DANA DESA BAGI MASYARAKAT MISKIN TERKENA DAMPAK PANDEMI COVID-19 DI DESA KALIWUNGU KECAMATAN BRUNO KABUPATEN PURWOREJO - Kofsatun Mardiyah (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2021)
Early 2020, the COVID-19 pandemic will become a world problem. Even some governments in the world are overwhelmed but continue to work to overcome the spread of this virus, as well as to overcome its various effects. One of the impacts caused by the Covid-19 pandemic is an economic factor. In Indonesia, there is no exception, as a result of this pandemic the people's economy has declined. And to overcome this, one of the efforts made by the Indonesian government is to refocus the budget from various existing budget items. And one of the budget items that is also being refocused is the Village Fund. Village funds, which are actually intended for village development and development, have been converted into cash assistance funds called Village Fund Direct Cash Assistance (BLT Dana Desa). In terms of its effectiveness, this program still raises many questions. Therefore this research was conducted to see the effectiveness of the Village Fund Direct Cash Assistance program. This research was conducted in the village of Kaliwungu, Bruno, Purworejo Regency. The research findings show that the effectiveness of this program, especially for the poor, is felt to be very beneficial for them, and most people support the program carried out by the central government.